Twenty years of progress in angiotensin converting enzyme 2 and its link to SARS-CoV-2 disease - Ferrario, Carlos M.; Ahmad, Sarfaraz; Groban, Leanne (Clinical science (1979), 2020)
The virulence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the aggressive nature of the disease has transformed the universal pace of research in the desperate attempt to seek effective therapies to halt the morbidity and mortality of this pandemic. The rapid sequencing of the SARS-CoV-2 virus facilitated identification of the receptor for angiotensin converting enzyme 2 (ACE2) as the high affinity binding site that allows virus endocytosis. Parallel evidence that coronavirus disease 2019 (COVID-19) disease evolution shows greater lethality in patients with antecedent cardiovascular disease, diabetes, or even obesity questioned the potential unfavorable contribution of angiotensin converting enzyme (ACE) inhibitors or angiotensin II (Ang II) receptor blockers as facilitators of adverse outcomes due to the ability of these therapies to augment the transcription of Ace2 with consequent increase in protein formation and enzymatic activity. We review, here, the specific studies that support a role of these agents in altering the expression and activity of ACE2 and underscore that the robustness of the experimental data is associated with weak clinical long-term studies of the existence of a similar regulation of tissue or plasma ACE2 in human subjects.